A PRAGMATIC ANALYSIS ON COMMANDINGUTTERANCES IN THE GREAT DEBATERS MOVIE MANUSCRIPT - Widyarini, Yunisa (2007)
This research studies about commanding utterances in The Great Debaters Movie Manuscript. The objectives of the research are to describe the linguistic form and the implicature (implied meaning) of commanding utterances. The type of this research is descriptive qualitative research. The method of collecting data is observation and analyzing document by selecting the commanding utterances which can be found in The Great Debaters Movie Manuscript. To achieve the objectives of the study, the writer identifies the data based on the linguistic form and describes the implicature. The result of the data analysis shows that there are three forms of commanding utterances, namely declarative sentence (32.4%), imperative sentence (64.7%) and interrogative sentence (2.9%). Meanwhile the implicature is classified into two: Conventional Implicature which includes ordering (38.2% ), requesting (14.7%) and Conversational Implicature which covers Ordering (20.6%), prohibiting (11.8%), requesting (5.9%) and suggesting (8.8%).